Language Crime: Potential Defamation and Criminality in Fake News From a Forensic Linguistic Perspective - Khoirunnisa, Krismonika; Kulsum, Umi; Roesmiati, Dian (Program Studi Sastra Indonesia Universitas Jenderal Soedirman, 2023)
Language and media are interesting topics to study. Considering that language has criteria in society, the media will not be spared as a means of communication. Over time, language has many variations that cannot be seen from just one aspect, but needs to be seen from other accompanying aspects. One of them is the “Why” aspect. The